LEGAL PROTECTION OF MARRIAGE AGREEMENTS FOR HUSBAND AND WIFE - Hartini, Sri Iin (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
A marriage agreement is made with the aim of providing legal protection for parties with good intentions from other parties with bad intentions. In addition to separating assets brought before marriage, marriage agreements made before and after marriage are basically aimed at separating assets brought and joint assets due to legal consequences that occur to their marital assets. A marriage agreement made before marriage aims to prevent problems arising regarding assets brought and joint assets so that a marriage agreement is needed as a legal basis for separating them. Meanwhile, a marriage agreement made after marriage is made with the aim of regulating the legal consequences that arise to their assets.